Tofacitinib and budesonide treatment affect stemness and chemokine release in IBD patient-derived colonoids - Arun Sridhar; Ingunn Bakke; Shreya Gopalakrishnan; Nimo Mukhtar Mohamud Osoble; Emilie Prytz Hammarqvist; Henrik P. Sahlin Pettersen; Arne Kristian Sandvik; Ann Elisabet Østvik; Marianne Doré Hansen; Torunn Bruland (Scientific Reports)
Abstract Restoration of the intestinal epithelial barrier is crucial for achieving mucosal healing, the therapeutic goal for inflammatory bowel disease (IBD). During homeostasis, epithelial renewal is maintained by crypt stem cells and progenitors that cease to divide as they differentiate into mature colonocytes. Inflammation is a major effector of mucosal damage in IBD and has been found to affect epithelial stemness, regeneration and cellular functions. However, the impact of immune cell-modulating IBD drugs on epithelial homeostasis and repair is poorly understood. It is likely that these drugs will have distinct mechanisms of action (MOA) in intestinal epithelium relevant for homeostasis that will vary among patients. We investigated cellular effects of pan-Janus Kinase (JAK) inhibitor tofacitinib and the corticosteroid budesonide on uninflamed and TNF + Poly(I:C) stimulated human colon organoids (colonoids) from healthy donors and IBD-patients. Our findings reveal that although both tofacitinib and budesonide exhibit anti-inflammatory effects, tofacitinib increased colonoid size and proliferation during differentiation, and promoted epithelial stemness. In contrast, budesonide decreased colonoid size and showed no consistent effect on proliferation or stemness. Our study demonstrates the value of employing human colonoids to investigate how IBD drugs affect intestinal epithelial cells and inter-individual variations relevant to mucosal healing and personalized IBD treatment.